Place, peace and security in Solomon Islands. (December 2020) - Higgins, Kate
This article examines the relationship between place and peace and security in Solomon Islands. Place is understood not only as a geographical location, but as a social, material and symbolic arena where constructions of what constitutes peace and security are continually remade. Place-based constructions of peace and security challenge pervasive spatial assumptions which underpin dominate security discourses about post-conflict Solomon Islands, assumptions which view security as a public good delivered by centralised state institutions to the peripheries. Employing a case study of one particular place, the Gela Group of Islands, this article describes place-based practices, processes, institutions and ideals of peace in contrast to a state ideal of security and argues that far from existing in separate spaces, both place-based and state-based forms of security are in constant interaction and shape each other over time. This article suggests that a way forward in increasing peace and security outcomes in Solomon Islands is to focus on the relationship between place-based forms of security and the state. Doing so acknowledges the political, relational and spiritual worlds of people of place, worlds which fundamentally shape peace and livelihood outcomes, and which require a different understanding of the spatial make-up of the state.